Psycholinguistic Barriers in Foreign Language Communication: A Study of Students at UIN Alauddin Makassar - Andi Nurbaethy; Abd. Muis Said (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
This study examines the psycholinguistic barriers encountered by university students in foreign language communication and explores strategies for overcoming these barriers. The research was conducted at UIN Alauddin Makassar, involving students from four language-related departments: English Education, Arabic Education, English Literature, and Arabic Literature. Employing a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that psycholinguistic barriers in foreign language communication can be categorized into two main forms: barriers in language production and barriers in language perception. Language production barriers include difficulties in phonological accuracy, inappropriate intonation and stress, morphological and syntactic interference from the first language, and limited alignment between verbal expressions and non-verbal cues. Meanwhile, language perception barriers involve difficulties in maintaining concentration on conversational topics, predicting interlocutors’ intentions, and providing appropriate responses to communicative acts. Furthermore, these barriers are influenced by both linguistic factors—such as limited mastery of phonology, morphology, syntax, and semantics—and non-linguistic factors, including low motivation, high anxiety, and fear of making mistakes. To address these challenges, the study proposes several strategies, including strengthening students’ linguistic competence, providing psycholinguistic support to reduce anxiety, and creating supportive foreign language environments. The study highlights the importance of integrating psycholinguistic perspectives into foreign language instruction to enhance students’ communicative competence.